NUCLEAR THREAT IN INDONESIA'S SOVEREIGN RIGHTS IMPACTED BY THE AUKUS AGREEMENT - Fikri, Ahmad; Maaggazing, Fernand Faktur Daeng; Danial, Danial; Rohani, Aceng Asnawi; Aslamiyah, Mujadiddah; Mohas, Muhyi (Sriwijaya Crimen and Legal Studies, 2024)
The AUKUS agreement, a trilateral pact between Australia, the United Kingdom, and the United States, has increased tensions between Indonesia and Australia. The deal focuses on enhancing defense capabilities, particularly by developing nuclear-powered submarines. This has broader geopolitical implications for the Asia-Pacific region and affects bilateral relations between Indonesia and Australia. The two countries have historically shared strong economic ties and cooperation in various sectors but have also faced disagreements, particularly regarding issues like West Papua and regional security alignments. Indonesia views Australia's participation in AUKUS as potentially increasing foreign military presence in the region, raising concerns about sovereignty and maritime security. The focus on nuclear submarines also raises legal and environmental considerations under international maritime law, particularly concerning exclusive economic zones (EEZs) and resource sovereignty. With the world's largest maritime territory, Indonesia emphasizes adherence to UNCLOS and calls for dialogue to manage these tensions peacefully. Some perceive the AUKUS alliance as a response to balance China's growing power, but this polarizes regional perspectives, with Southeast Asian nations expressing mixed reactions ranging from support to apprehension. The alliance's implications extend beyond military capability enhancement to include technological cooperation and regional stability efforts. In conclusion, AUKUS aims to bolster security and technological advancement in the Indo-Pacific. Still, its implementation requires careful navigation of legal, environmental, and geopolitical complexities to mitigate potential regional tensions and uphold international norms.